2006
DOI: 10.1007/s10562-005-9186-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel TiO2 by Mechanical Alloying and Heat Treatment-derived Nanocomposite of TiO2 and NiTiO3

Abstract: A novel nanocomposite titanium dioxide powders were synthesized by mechanical alloying and heat treatment. The absorption threshold of the nanocomposite TiO 2 moved to a longer wavelength and the photoreactivity was dramatically enhanced. Also the new absorption was believed to be induced by the trapping band gap between the valence and conduction bands of nanocomposite TiO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…The presence of transmittance bands between 3400 and 3600 cm −1 are seen, which increased by doping Ce in TiO 2 while transmittance bands at 1625 cm −1 decreases with increase in doping Ce content in TiO 2 . These bands are attributed to the stretching vibrations of the O-H groups and the bending vibrations of the adsorbed water molecules, respectively [24,25]. A band between 650 and 830 cm −1 is seen which is attributed to different vibrational modes of TiO 2 .…”
Section: Ftir Absorption Analysismentioning
confidence: 93%
“…The presence of transmittance bands between 3400 and 3600 cm −1 are seen, which increased by doping Ce in TiO 2 while transmittance bands at 1625 cm −1 decreases with increase in doping Ce content in TiO 2 . These bands are attributed to the stretching vibrations of the O-H groups and the bending vibrations of the adsorbed water molecules, respectively [24,25]. A band between 650 and 830 cm −1 is seen which is attributed to different vibrational modes of TiO 2 .…”
Section: Ftir Absorption Analysismentioning
confidence: 93%
“…The slight increase of -axis parameter with increasing NiO concentrations ( Table 2) suggested that minor fraction of Ni 2+ replaces Ti 4+ . This was achieved due to similar ionic radius of both Ni 2+ (0.72Å) and Ti 4+ (0.68Å) [38]. It is also speculated that Ni 2+ was not incorporated interstitially because the lattice constants did not remain constant for higher NiO concentrations.…”
Section: Resultsmentioning
confidence: 95%
“…The peak at 638.8 nm could be originated from a deep level above the Fermi level, which might have originated from the cationic doping by silicone or nickel doping [5,43,44].…”
Section: Resultsmentioning
confidence: 99%
“…Carbon is diffused into the multicomponent layer and is dissolved into nickel, which assists in the formation of nickel nanoparticles that induce the conversion of TiN into TiC x N y , and then the conversion of TiC x N y into TiO 2 − x N y C z sequentially. Based on thermodynamics, titanium oxide formation from titanium carbide (−553 kJ/mol-O 2 ) is easier than that from titanium nitride (−491 kJ/mol-O 2 ) [44]. The carbon-assisted conversion of TiN into TiO 2 − x triggers to form the nucleation of nanowires in the buried layer as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%